Laminated cell and preparation method thereof

By combining the use of alcohols and polar organic solvents by the evaporation-solution method, the light management problems and incomplete reactions of perovskite/silicon tandem solar cells on industrial textured silicon are solved, and efficient perovskite layer preparation and light management effects are achieved.

CN119654038APending Publication Date: 2025-03-18JIANGSU SHENGKAI NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411948301.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing perovskite/silicon tandem solar cells have poor light management on industrial texture silicon, and the organic ammonium halide salt reacts completely with the inorganic salt in the evaporation process, making it difficult to achieve efficient perovskite layer preparation.

Method used

Using the combined method of evaporation-solution method, the inorganic salt is first deposited by the evaporation method to form an evaporation layer, and then deposited organic ammonium salts by the solution method to react with the inorganic salts in the evaporation layer to form a perovskite light absorbing layer. Alcohols and organic solvents containing N and O atoms are used as solvents to enhance the permeability and thorough reaction of the organic ammonium salt.

Benefits of technology

The perovskite layer is realized on the structure of crystalline silicon suede pyramid, avoiding the problem of difficult evaporation pressure, and improving the reaction degree and light management effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654038A_ABST
    Figure CN119654038A_ABST
Patent Text Reader

Abstract

The invention relates to a laminated cell and a preparation method thereof, and the preparation method comprises the steps: after preparing a carrier transport layer on a crystalline silicon cell, evaporating inorganic salt to form an evaporation layer, the inorganic salt containing PbI2 and CsBr; the organic ammonium salt solution comprises a solute and a solvent, the solute comprises an organic ammonium salt, the organic ammonium salt reacts with an inorganic salt to form a perovskite light absorption layer, the solvent comprises a first solvent and a second solvent, the first solvent is an alcohol solvent, and the second solvent is a polar solvent containing N or O atom lone pair electrons; the second solvent content is less than the first solvent content; the perovskite light absorption layer is formed by two steps of an evaporation-solution method, so that shape-preserving deposition of the perovskite layer on a crystalline silicon textured pyramid structure can be ensured, and the problem that the evaporation pressure of organic salt is difficult to adjust in total evaporation can be avoided; in the second-step solution method, two solvents are used to form a mixed solvent to dissolve the organic ammonium salt, so that permeation of the organic ammonium salt in the evaporation layer is enhanced, and PbI2 reaction is more thorough.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a stacked battery and a preparation method thereof, belonging to the field of solar cells. Background Art

[0002] Perovskite / silicon tandem solar cells have been widely studied because of their theoretical conversion efficiency far exceeding that of silicon cells. The high-efficiency or large-area monolithic perovskite / silicon tandem cells reported so far are mainly manufactured on silicon bottom cells, with polished or submicron textured front sides (pyramid size is usually less than 1 μm) to accommodate the solution process for depositing perovskite films. However, this requires adding extra polishing steps or modifying the pyramid size in the established standard industrial process, and the light management is poorer than that of industrial textured silicon. The evaporation process in the currently commonly used evaporation-solution two-step method will result in incomplete reaction between organic ammonium halide salts and inorganic salts due to the dense structure of the evaporation layer. Therefore, seeking a perovskite preparation method compatible with industrial textured silicon will help achieve strong light management at a lower cost. Summary of the invention

[0003] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a stacked battery and a stacked battery obtained by the method. In the preparation method, an inorganic salt is deposited by an evaporation method to form an evaporation layer, and then an organic ammonium salt is deposited by a solution method, so that the organic ammonium salt can penetrate into the evaporation layer to react and improve the degree of reaction. The organic ammonium salt solution uses an alcohol solvent and an organic solvent containing N and O atoms and having lone pairs of electrons as solvents. The two solvents cooperate with each other to coat the organic ammonium salt solution around the inorganic salt, so that the reaction is more thorough.

[0004] The solution adopted by the present invention is: a method for preparing a laminated battery, comprising the following steps S01 obtains crystalline silicon solar cells; S02 preparing a first carrier transport layer on the light absorbing surface of the crystalline silicon solar cell, or preparing a first intermediate layer on the light absorbing surface of the crystalline silicon solar cell before preparing the first carrier transport layer, wherein the light absorbing surface of the crystalline silicon solar cell has a suede structure; S03 evaporating an inorganic salt on the first carrier transport layer to form an evaporation layer, wherein the inorganic salt contains PbI2 and CsBr; S04 coating the evaporated layer with an organic ammonium salt solution, wherein the organic ammonium salt solution comprises a solute and a solvent, wherein the solute is an organic ammonium salt, and the organic ammonium salt reacts with the inorganic salt to form a perovskite light-absorbing layer, and the solvent comprises a first solvent and a second solvent, wherein the first solvent is an alcohol solvent, and the second solvent is an organic solvent containing lone pairs of electrons of N or O atoms, and the content of the second solvent is less than the content of the first solvent; S05 preparing a second carrier transport layer on the perovskite light absorption layer, or preparing a second intermediate layer on the perovskite light absorption layer and then preparing the second carrier transport layer; S06: preparing an electrode on the second carrier transport layer or preparing an electrode after preparing a third intermediate layer on the second carrier transport layer.

[0005] The inorganic salts are PbI2 and CsBr. The structure of the evaporated PbI2 is very dense, so the organic ammonium salt solution cannot penetrate and therefore cannot fully react with PbI2. + The introduction of can make the structure of PbI2 loose and porous, promoting the penetration of organic ammonium salt solution. The preferred evaporation rate ratio of PbI2 to CsBr is 4:0.8, and more preferably 1:0.1, because the PbI2 crystals are larger under this ratio, and Cs + The content is moderate, which increases the porosity between PbI2 grains. When the amount of CsBr is too much, the perovskite will introduce significant lattice stress and defects due to the large difference in ionic radius, which will lead to perovskite phase separation.

[0006] As a preferred embodiment, the volume ratio of the first solvent to the second solvent is (96:4) to (99.5:0.5).

[0007] As a preferred embodiment, the second solvent is a combination of one or more of N,N-dimethylformamide, dimethyl sulfoxide, 1,4-butyrolactone, N-methylpyrrolidone, γ-valerolactone, and dimethyl isosorbide.

[0008] As a preferred embodiment, the organic ammonium salt includes MAX and FAX, wherein X is a halogen. The molar ratio of FAX to MAX can be 2:1 to 4:1, and the specific ratio can be adjusted according to the band gap of the perovskite. FAX includes FAI and FABr; MAX includes MABr and MACl, MABr is used to adjust the band gap of the perovskite, and the addition of MACl can promote crystallization.

[0009] As a preferred embodiment, the band gap of the perovskite light-absorbing layer formed by the reaction of the organic ammonium salt and the inorganic salt is 1.67 eV-1.69 eV.

[0010] As a preferred embodiment, the first intermediate layer is one, two or more of a tunnel junction, a modification material layer and a buffer layer; the second intermediate layer is one or two of a modification material layer and a buffer layer; the third intermediate layer is one or two of a modification material layer and a buffer layer.

[0011] As a preferred embodiment, the first carrier transport layer is a hole transport layer, and the hole transport layer material is MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid), Me-4PACz ((4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid), PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), 4PADCB ((4-(7h-dibenzo[c,g]carbazole-7-yl)butyl)phosphonic acid) or nickel oxide; The second carrier transport layer is an electron transport layer, and the electron transport layer is fullerene (C 60 ) and its derivatives.

[0012] As a preferred embodiment, the inorganic salt includes PbI2 and CsBr, and the evaporation process is: the PbI2 evaporation rate is 1~4Å / s, the CsBr evaporation rate is 0.1~0.8Å / s, and the total film thickness of the evaporated layer is 600nm.

[0013] The present invention also provides a stacked cell, which uses a crystalline silicon solar cell as a bottom cell and a perovskite solar cell as a top cell, wherein the light-absorbing surface of the bottom cell is a velvet structure, and the preparation process of the perovskite solar cell is as follows: S01: preparing a first carrier transport layer on the light absorption surface of the crystalline silicon solar cell, or preparing the first carrier transport layer after preparing a first intermediate layer on the light absorption surface of the crystalline silicon solar cell; S02 evaporating an inorganic salt on the first carrier transport layer to form an evaporation layer, wherein the inorganic salt contains at least PbI2 and CsBr; S03 coating the evaporated layer with an organic ammonium salt solution, wherein the organic ammonium salt solution comprises a solute and a solvent, wherein the solute is an organic ammonium salt, and the organic ammonium salt reacts with the inorganic salt to form a perovskite light-absorbing layer, and the solvent comprises a first solvent and a second solvent, wherein the first solvent is an alcohol solvent, and the second solvent is an organic solvent containing lone pairs of electrons of N or O atoms, and the content of the second solvent is less than the content of the first solvent; S04 preparing a second carrier transport layer on the perovskite light absorption layer, or preparing a second intermediate layer on the perovskite light absorption layer and then preparing the second carrier transport layer; S05: preparing a transparent electrode on the second carrier transport layer or preparing a transparent electrode after preparing a third intermediate layer on the second carrier transport layer.

[0014] The battery is prepared in such a way that the volume ratio of the first solvent to the second solvent is preferably 99.5:0.5 to 96:4. The second solvent is preferably a combination of one or more of N,N-dimethylformamide, dimethyl sulfoxide, 1,4-butyrolactone, N-methylpyrrolidone, γ-valerolactone, and dimethyl isosorbide (DMI). The inorganic salt is preferably PbI2 and CsBr. The organic ammonium salt includes MAX and FAX, wherein X is a halogen.

[0015] As a preferred embodiment, the first intermediate layer is one, two or more of a tunnel junction, a modification material layer and a buffer layer; the second intermediate layer is one or two of a modification material layer and a buffer layer; the third intermediate layer is one or two of a modification material layer and a buffer layer.

[0016] As a preferred embodiment, the first carrier transport layer is a hole transport layer, and the hole transport layer material is MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid), Me-4PACz ((4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid), PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), 4PADCB ((4-(7h-dibenzo[c,g]carbazole-7-yl)butyl)phosphonic acid) or nickel oxide; the second carrier transport layer is an electron transport layer, and the electron transport layer is fullerene (C 60 ) and its derivatives.

[0017] The beneficial effects produced by the present invention include: the present invention adopts a two-step evaporation-solution method to form the perovskite light-absorbing layer, which can not only ensure the conformal deposition of the perovskite layer on the crystalline silicon velvet pyramid structure, but also avoid the problem that the evaporation pressure of the organic salt is difficult to adjust during full evaporation; in the solution method, two solvents are used to form a mixed solvent to dissolve the organic ammonium salt, which is beneficial to enhance the penetration of the organic ammonium salt in the evaporated layer and make the PbI2 reaction more thorough. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The structure diagram of the laminated battery prepared in Example 1; Figure 2 JV curves of the laminated batteries obtained in Example 1 and Comparative Example 1; Figure 3 Cross-sectional SEM images of the perovskite layers obtained in Example 1 and Comparative Example 1; Figure 4 JV curves of the laminated batteries obtained in Example 2 and Comparative Example 2. DETAILED DESCRIPTION

[0019] The present invention will be further explained in detail below in conjunction with specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Unless otherwise specified, any range recorded in the present invention includes any end value and any numerical value between the end values ​​and any sub-range constituted by the end value or any numerical value between the end values. All raw materials of the present invention are not particularly limited to their purity, and the present invention preferably adopts analytical pure. All raw materials of the present invention, their sources and abbreviations all belong to conventional sources and abbreviations in this area, and are all clear and definite in the field of their related uses. Those skilled in the art can purchase or prepare them from commercially available according to the abbreviations and corresponding uses. All percentages of the present invention are volume percentages unless otherwise specified.

[0020] "At least one" means one or more, and "more" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the previous and next associated objects are in an "or" relationship. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, at least one of a, b or c can mean: a, b, c, the combination of a and b, the combination of a and c, the combination of b and c, or the combination of a, b and c, where a, b, c can be single or plural.

[0021] The present invention provides a method for preparing a stacked battery, wherein the stacked battery uses a crystalline silicon battery as a bottom battery and a perovskite battery as a top battery, and the two batteries are connected in series or in parallel to form a stacked battery, and the preparation method comprises the following steps: S01 Obtain a crystalline silicon solar cell, the crystalline silicon solar cell is purchased or prepared from raw materials, the light-absorbing surface of the crystalline silicon solar cell is a velvet surface, and is provided with a pyramid structure; S02 preparing a first carrier transport layer on the light absorbing surface of the crystalline silicon solar cell, wherein the first carrier transport layer is directly disposed on the light absorbing surface or indirectly disposed on the light absorbing surface via a first intermediate layer, wherein the first intermediate layer may be a tunneling layer, a buffer layer or a passivation material, a modification material, etc.; S03 vapor-depositing an inorganic salt on the first carrier transport layer to form a vapor-deposited layer, wherein the inorganic salt contains at least PbI2 and CsBr; the vapor-deposited layer is directly or indirectly disposed on the first carrier transport layer, and the direct arrangement is to place the inorganic salt in direct contact with the first carrier transport layer, and the indirect arrangement is to place a modification layer or other material layer on the first carrier transport layer and then deposit the vapor-deposited layer; S04 coating an organic ammonium salt solution on the vapor deposition layer, wherein the organic ammonium salt solution includes a solvent and a solute, wherein the solute includes an organic ammonium salt, and may contain only the organic ammonium salt, or may contain a modification material, a purification material, etc. on the basis of the organic ammonium salt; the solvent includes a first solvent and a second solvent, wherein the first solvent is an alcohol solvent, and the second solvent is a polar solvent containing lone pairs of electrons of N or O atoms, and the content of the second solvent is less than that of the first solvent; after coating the organic ammonium salt solution, the organic ammonium salt reacts with the inorganic salt to form a perovskite, thereby obtaining a perovskite light-absorbing layer; S05 directly or indirectly stacking a second carrier transport layer on the perovskite light absorption layer, directly stacking the second carrier transport layer to the perovskite light absorption layer, and indirectly stacking the second carrier transport layer on the perovskite light absorption layer after a modification layer and / or a buffer layer and / or other material layer are stacked on the perovskite light absorption layer; S06 directly or indirectly disposing an electrode on the second carrier transport layer. Directly disposing an electrode on the second carrier transport layer. Indirectly disposing an electrode after disposing a transparent conductive layer and / or a buffer layer and / or other material layer on the second carrier transport layer.

[0022] The first carrier transport layer is a hole transport layer, and the second carrier transport layer is an electron transport layer.

[0023] When preparing stacked cells, it is necessary to deposit perovskite cells on crystalline silicon solar cells. In order to improve the light absorption efficiency of crystalline silicon cells, their light absorption surface is generally set to a velvet structure. The deposition method of the perovskite light absorption layer on the velvet surface of the crystalline silicon solar cell can be gas phase deposition such as vacuum evaporation. This deposition method is scalable, can improve the quality of the film, and is not affected by the velvet pyramid structure. It can form a film layer with uniform thickness, so that the perovskite light absorption layer inherits the velvet structure with anti-reflection effect of the crystalline silicon cell. If full evaporation is used to form the perovskite light absorption layer, the following problems will arise: 1. The inorganic salt and organic ammonium salt are co-evaporated to form the perovskite light absorption layer. It is necessary to place the inorganic salt PbX2 and the organic ammonium halide precursor in different crucibles and perform thermal evaporation at the corresponding sublimation temperature in a high vacuum chamber. However, the evaporation of inorganic salts such as PbX2 can be precisely controlled by monitoring the deposition rate, while the evaporation rate of organic ammonium halides is difficult to control due to their high vapor pressure; 2. The high vapor pressure of the evaporated organic ammonium halide salt makes it difficult to adjust the vacuum chamber pressure, further reducing the deposition rate and causing great pressure.

[0024] The present invention adopts the form of evaporation-solution combination, that is, inorganic salts such as PbX2 are deposited by evaporation, and organic ammonium salts are deposited by solution method. This method can not only retain the velvet structure by evaporation method, but also improve the reaction degree by solution method. However, since the film layer structure formed by evaporation is relatively dense, it is difficult for inorganic salts and organic ammonium salts to react thoroughly. In the solution method, the present invention uses a mixed solvent formed by a first solvent and a second solvent as an organic ammonium salt solvent, the first solvent is an alcohol solvent, which can fully dissolve the organic ammonium salt, and the second solvent is a polar solvent containing lone pairs of electrons of N or O atoms. The lone pairs of electrons on N and O atoms can be used as electron donors to coordinate with the Pb atoms in PbI2: Pb atoms have empty electron orbits due to their electronic configuration characteristics, and can accept lone pairs of electrons on N or O atoms, thereby forming a coordination bond of N→Pb or O→Pb. This coordination allows polar solvent molecules to be tightly combined with lead atoms, thereby surrounding PbI2 to form a solvation layer, and then PbI2 can be stably present in the solvent. With the help of the second solvent, the organic ammonium salt solution can gradually "dissolve" PbI2 in the process of penetrating into the evaporated layer, making the reaction between the organic ammonium salt and the inorganic salt in the evaporated layer more thorough, thereby reducing the PbI2 residue at the bottom of the perovskite layer after the reaction is completed.

[0025] The first solvent and the second solvent are mixed in the above ratio to form a mixed solvent, and the volume ratio of the first solvent to the second solvent is 96:4~99.5:0.5. The volume ratio of the first solvent to the second solvent can be 99.5:0.5, 99:1, 98.5:1.5, 98:2, 97.5:2.5, 97:3, 96:4. The first solvent can be one of ethanol and isopropanol. Alcohols are considered to be effective solvents for dissolving organic ammonium salts in the two-step method. The second solvent can be N, N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), 1,4-butyrolactone (GBL), N-methylpyrrolidone (NMP), γ-valerolactone (GVL), dimethyl isosorbide (DMI) and other polar solvents containing lone pairs of electrons of N and O atoms, or a mixture of two, three or more thereof. If the proportion of the second solvent is too low, the effect of promoting the penetration of organic ammonium salt is not obvious; if the proportion of the second solvent is too high, a large amount of inorganic salt will be dissolved, thereby losing the shape retention on the textured silicon and causing leakage. The preferred second solvent is DMI, and the molecular structure of DMI is Its structure has a unique chirality, which makes its molecular polarity higher than many solvents except NMP and DMF. In addition, DMI has two carbonyl O atoms and ether bond O atoms, and its molecules contain more O atoms with lone pairs of electrons than other solvents, so it has a strong "coating" ability for PbI2 molecules. In addition, DMI is also a green biomass solvent, non-toxic and harmless to the human body. It can be used in an air environment and is suitable for the current industrialized slit coating process.

[0026] When the second solvent is DMF or DMSO, the ratio of the first solvent to the second solvent is preferably 99:1 to 99.9:0.5. At this time, the second solvent has a strong polarity, and the lone pair electrons in the N and O atoms in the molecular structure have a strong coordination effect with Pb2+. Selecting 99.9:0.5 to 99:1 is conducive to balancing the polarity of the solvent, so that the solution penetration effect can be achieved and the inorganic salt can be prevented from dissolving and falling off. When the second solvent is GVL, the ratio of the first solvent to the second solvent is preferably 96:4.

[0027] The crystalline silicon cell used as the substrate can be a crystalline silicon cell such as HJT, HBC, TOPCon, etc. The deposited hole transport material can be one of MeO-2PACz ([2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid), Me-4PACz ((4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid), PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), 4PADCB ((4-(7h-dibenzo[c,g]carbazole-7-yl)butyl)phosphonic acid), nickel oxide, or a combination of two or more thereof; the deposition method used can be solution coating (spin coating, scraper coating, spray coating) or vacuum evaporation. Me-4PACz can effectively increase the open circuit voltage (V oc MeO-2PACz has good coverage on the substrate, which is beneficial to improve the wettability of the material on the perovskite layer, thereby improving the fill factor and short-circuit current of the battery. For the stacked battery, the present invention preferably uses 4PADCB. 4PADCB can not only improve the film coverage and surface wettability, but also improve the open circuit voltage (V oc ) and fill factor (FF). The steps of depositing the perovskite light absorbing layer on the hole transport layer can be specifically as follows: a. Co-evaporating an inorganic salt at a certain rate to form a vapor deposition layer, wherein the inorganic salt components are PbI2 and CsBr; b. Prepare organic ammonium salt solution: prepare MAX and FAX solutions, where MAX includes one or all of MABr and MACl, and FAX includes one or all of FAI and FABr. The solvent is ethanol or isopropanol, to which 0.5%-4% polar solvent containing lone pair electrons of N or O atoms is added, and stirred at room temperature until completely dissolved; c. coating the evaporated layer with an organic ammonium salt; d. Annealing in air and cooling to obtain a perovskite light-absorbing layer with a band gap of 1.6-1.8 eV.

[0028] After the perovskite light absorbing layer is prepared, a modification material layer (passivation layer) is deposited. The deposition method is coating, which can be scraping, spin coating, spraying, etc. The preparation method of the modification layer is: a. Dissolve the modified material in isopropanol and stir to form a 0.5mM~0.5M solution (can be 0.1M, 0.2M, 0.3M, 0.4M, 0.5M); b. Spin-coat the modified material solution on the perovskite light-absorbing layer at a speed of 1000-5000 rpm (can be 1000 rpm, 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm) for 10-50 s (can be 10 s, 20 s, 30 s, 40 s, 50 s), and then anneal in a glove box at 60-100 ° C (can be 60 ° C, 70 ° C, 80 ° C, 90 ° C, 100 ° C) for 2-6 min (2 min, 3 min, 4 min, 5 min, 6 min); The electron transport layer is deposited on the passivation layer by coating or vacuum evaporation. The electron transport layer material is fullerene (C 60 ) and its derivatives; A SnO2 buffer layer is deposited on the electron transport layer by atomic layer deposition (ALD); Depositing TCO material on the buffer layer to form a transparent electrode layer, which may be ITO or IZO, by magnetron sputtering; Cu, Ag or Au is deposited on the transparent electrode to form a metal electrode layer by vacuum evaporation.

[0029] The following is further described in the form of specific embodiments. Example

[0030] The method for preparing the stacked battery comprises the following steps: S01 Get bottom battery HJT battery is used as the bottom battery. The parameters of the HJT bottom battery used are as follows: V oc 0.70~0.74V, J sc 38~39.5mA / cm 2 , FF is 80~85%, and the photoelectric conversion efficiency (PCE) is 24~25%. The size of the bottom cell is 3cm*3cm. The n-side of the bottom cell is plated with a 15nm ITO tunnel junction, and the back side is provided with an Ag electrode. The prepared bottom cell is placed in a UV ozone treatment device for 15 minutes for standby use.

[0031] S02 Preparation of hole transport layer (1) Mix 0.5 mg of 4PADCB with 1 mL of ethanol solution to obtain a 0.5 mg / mL 4PADCB solution, filter the solution using a 0.45 μm filter element to remove large particles, and set the filtered solution aside; (2) Spin-coat the filtered solution onto the bottom cell at a rate of 4000 rpm for 30 s. (3) Annealing at 120°C for 20 min to obtain a 4PADCB hole transport layer.

[0032] Preparation of S03 perovskite light absorbing layer (1) Evaporation of inorganic salts: A thermal evaporation process is used to form a perovskite inorganic layer on the substrate. In this embodiment, a dual-source co-evaporation process is used, the first material source is PbI2, and the second material source is CsBr. The evaporation rate of PbI2 is 4Å / s, and the evaporation rate of CsBr is 0.8Å / s. The total thickness of the evaporation layer is 600nm.

[0033] (2) Preparation of organic ammonium salt solution: prepare a mixed solution of MAX and FAX, wherein MAX includes MABr and MACl, and FAX includes FAI and FABr. The concentration of FAI is 0.131 M, the concentration of FABr is 0.318 M, the concentration of MABr is 0.085 M, and the concentration of MACl is 0.10 M. The solvents are isopropanol and DMF, and the volume ratio of the two is 99:1.

[0034] (3) Organic ammonium salt coating: This process is carried out in a glove box by spin coating. The prepared organic ammonium salt solution is spin coated on the inorganic layer at a spin coating rate of 3000 rpm and a spin coating time of 30 seconds. The film obtained after coating is annealed in air with an air humidity of 35-40%. The temperature and time are 160°C for 15 minutes. The film is cooled and set aside.

[0035] Preparation of S04 Modified Layer (1) Preparation of modification layer solution: This example uses EDAI2 (ethylenediamine dihydroiodide) as an example. EDAI2 is prepared into a solution with a concentration of 0.5 mg / mL and dissolved under ultrasonic vibration for 30 minutes.

[0036] (2) Spin coat the EDAI2 solution on the perovskite light absorbing layer at a speed of 4000 rpm for 30 seconds, and then anneal in a glove box at 100°C for 1 minute. The film thickness is 3~5 nm.

[0037] Preparation of S05 electron transport layer Using vacuum evaporation equipment, C is evaporated by thermal evaporation. 60 The material is used to form a 15nm electron transport layer on the perovskite light absorption layer. The evaporation rate is 0.2Å / s.

[0038] Preparation of S06 buffer layer: SnO2 was prepared as a buffer layer using an atomic layer deposition device (ALD) with the sources being tetrakis(dimethylaminotin) (tdma-sn) and deionized water, and the thickness was 20 nm.

[0039] Preparation of S08 transparent electrode Using a magnetron sputtering device, 30 nm IZO was sputtered on SnO2 as a transparent electrode.

[0040] Preparation of S09 electrode A 150-200nm thick Ag gate line was deposited as an electrode by thermal evaporation at a rate of 0.2 Å / s. Example

[0041] The method for preparing the stacked battery comprises the following steps: S01 Get bottom battery HJT battery is used as the bottom battery. The bottom battery parameters of the HJT bottom battery used are: V oc 0.70~0.74V, J sc 38~39.5mA / cm 2 , FF is 80~85%, and the photoelectric conversion efficiency (PCE) is 24~25%. The size of the bottom cell is 210cm*105cm. The n-side of the bottom cell is plated with a 15nm ITO tunnel junction, and the back side is provided with an Ag electrode. The prepared bottom cell is placed in a UV ozone treatment device for 15 minutes for standby use.

[0042] S02 Preparation of hole transport layer The hole transport layer was prepared by evaporation, and the evaporation material was 2PACz. The specific process was as follows: the evaporation rate was 0.2Å / s, and the thickness was 5nm. The obtained film layer did not need annealing.

[0043] Preparation of S03 perovskite light absorbing layer (1) Evaporation of inorganic salts: A thermal evaporation process is used to form a perovskite inorganic layer on the substrate. Specifically, in this embodiment, a dual-source co-evaporation process is used, the first material source is PbI2, and the second material source is CsBr. The evaporation rate of PbI2 is 4Å / s, and the evaporation rate of CsBr is 0.8Å / s. The total thickness of the inorganic layer evaporation is 600nm.

[0044] (2) Preparation of organic ammonium salt solution: prepare a mixed solution of MAX and FAX, wherein MAX includes MABr and MACl, and FAX includes FAI and FABr. The concentration of FAI is 0.131 M, the concentration of FABr is 0.318 M, the concentration of MABr is 0.085 M, and the concentration of MACl is 0.10 M. The solvents are isopropanol and DMI, and the volume ratio of the two is 98:2.

[0045] (3) Organic ammonium salt coating: The prepared organic ammonium salt solution is spin-coated on the inorganic layer using a slit coating method. The specific process is as follows: With the assistance of N2 in the air, the organic ammonium salt solution is coated at a speed of 20 mm s −1The blade was coated with 200 μL of organic salt solution at a rate of 250 μm; the gap between the blade and the substrate was 250 μm, and the pressure of the N2 blade was 30 PSI. The ambient temperature was 25°C and the humidity was 35 to 40%. The film obtained after coating was annealed in air for 15 minutes at a temperature of 160°C. The film was cooled and set aside.

[0046] Preparation of S04 Modified Layer The modified layer was prepared by evaporation. The selected evaporation material was EDAI2. The specific process was as follows: the evaporation rate was 0.2Å / s and the thickness was 5nm. The obtained film was then annealed at 100℃ for 1min and cooled for use.

[0047] Preparation of S05 electron transport layer Using vacuum evaporation equipment, C is evaporated by thermal evaporation. 60 The material forms a 15nm electron transport layer on the perovskite light absorption layer. 60 The optical loss caused by the absorption or reflection of the incident light will increase, resulting in the circuit current (J sc ) is reduced. The evaporation rate is 0.2Å / s.

[0048] Preparation of S06 buffer layer: SnO2 was prepared as a buffer layer using an atomic layer deposition device (ALD) with the sources being tetrakis(dimethylaminotin) (tdma-sn) and deionized water, and the thickness was 20 nm.

[0049] Preparation of S08 transparent electrode Using a magnetron sputtering device, 30 nm IZO was sputtered on SnO2 as a transparent electrode.

[0050] Preparation of S09 electrode A 150-200nm layer of Ag was deposited as an electrode by thermal evaporation at a rate of 0.2 Å / s.

[0051] Comparative Example 1 The only difference from Example 1 is that no polar solvent DMF is added, that is, the solvent of the organic salt in S03 in Example 1 is pure isopropanol.

[0052] The photoelectric conversion efficiency of the perovskite solar cells of Example 1 and Comparative Example 1 was tested. Figure 2 It can be seen that the conversion efficiency of the perovskite solar cell in Example 1 is significantly improved compared with that in Comparative Example 1, indicating that the addition of DMF can effectively reduce the residual PbI2 and increase the short-circuit current (J sc ), thereby improving battery efficiency.

[0053] The cross-sectional SEM photos of the perovskite in Test Example 1 and Comparative Example 1 are as follows: Figure 3 As shown. The white part at the interface between the perovskite and the pyramid is PbI2. A large amount of PbI2 remains at the bottom in Comparative Example 1, while almost no PbI2 remains at the bottom in Example 1, indicating that the addition of DMF can effectively promote the penetration of organic ammonium salts and reduce the PbI2 residue at the bottom.

[0054] Comparative Example 2 The only difference from Example 2 is that no polar solvent DMI is added, that is, the solvent of the organic salt in S03 in Example 2 is pure isopropanol.

[0055] The photoelectric conversion efficiency of the perovskite solar cells of Example 2 and Comparative Example 2 was tested. Figure 2 It can be seen that the conversion efficiency of the perovskite solar cell in Example 2 is significantly improved compared with that in Comparative Example 2, indicating that the addition of DMI can effectively increase the short-circuit current (J sc ), thereby improving battery efficiency.

[0056] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing a laminated battery, characterized in that: The following steps are included S01 obtains crystalline silicon solar cells; S02 preparing a first carrier transport layer on the light absorbing surface of the crystalline silicon solar cell, or preparing a first intermediate layer on the light absorbing surface of the crystalline silicon solar cell before preparing the first carrier transport layer, wherein the light absorbing surface of the crystalline silicon solar cell has a suede structure; S03 evaporating an inorganic salt on the first carrier transport layer to form an evaporation layer, wherein the inorganic salt contains at least PbI2; S04 coating the evaporated layer with an organic ammonium salt solution, wherein the organic ammonium salt solution comprises a solute and a solvent, wherein the solute comprises an organic ammonium salt, and the organic ammonium salt reacts with the inorganic salt to form a perovskite light-absorbing layer, and the solvent comprises a first solvent and a second solvent, wherein the first solvent is an alcohol solvent, and the second solvent is a polar solvent containing lone pairs of electrons of N or O atoms, and the content of the second solvent is less than the content of the first solvent; S05 preparing a second carrier transport layer on the perovskite light absorption layer, or preparing a second intermediate layer on the perovskite light absorption layer and then preparing the second carrier transport layer; S06: preparing an electrode on the second carrier transport layer or preparing an electrode after preparing a third intermediate layer on the second carrier transport layer.

2. The method for preparing a laminated battery according to claim 1, characterized in that: The volume ratio of the first solvent to the second solvent is 96:4-99.5:0.

5.

3. The method for preparing a laminated battery according to claim 1, characterized in that: The second solvent is a combination of one or more of N,N-dimethylformamide, dimethyl sulfoxide, 1,4-butyrolactone, N-methylpyrrolidone, γ-valerolactone, and dimethyl isosorbide.

4. The method for preparing a laminated battery according to claim 1, characterized in that: The inorganic salt is a mixture of PbI2 and CsBr.

5. The method for preparing a laminated battery according to claim 1, characterized in that: The organic ammonium salt includes MAX and FAX, wherein X is a halogen, and the molar ratio of FAX to MAX is (2-4):

1.

6. The method for preparing a laminated battery according to claim 1, characterized in that: The band gap of the perovskite light-absorbing layer formed by the reaction of the organic ammonium salt and the inorganic salt is 1.6-1.8 eV.

7. The method for preparing a laminated battery according to claim 1, characterized in that: The first intermediate layer is one, two or more of a tunnel junction, a modification material layer and a buffer layer; the second intermediate layer is one or two of a modification material layer and a buffer layer; the third intermediate layer is one or two of a modification material layer and a buffer layer.

8. The method for preparing a laminated battery according to claim 1, characterized in that: The first carrier transport layer is a hole transport layer, and the hole transport layer material is one of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], (4-(7h-dibenzo[c,g]carbazole-7-yl)butyl)phosphonic acid, and nickel oxide, or a mixture of two or more thereof; The second carrier transport layer is an electron transport layer, and the electron transport layer is fullerene and its derivatives.

9. The method for preparing a laminated battery according to claim 1, characterized in that: The evaporation process of the inorganic salt is as follows: the evaporation rate of PbI2 is 1-4Å / s, the evaporation rate of CsBr is 0.1-0.8Å / s, and the thickness of the evaporation layer is 400-600nm.

10. A laminated battery, characterized in that: A crystalline silicon solar cell is used as a bottom cell, a perovskite solar cell is used as a top cell, and the light-absorbing surface of the bottom cell is a velvet structure. The preparation process of the perovskite solar cell is as follows: S01: preparing a first carrier transport layer on the light absorption surface of the crystalline silicon solar cell, or preparing the first carrier transport layer after preparing a first intermediate layer on the light absorption surface of the crystalline silicon solar cell; S02 evaporating an inorganic salt on the first carrier transport layer to form an evaporation layer, wherein the inorganic salt contains at least PbI2; S03 coating the evaporated layer with an organic ammonium salt solution, wherein the organic ammonium salt solution comprises a solute and a solvent, wherein the solute is an organic ammonium salt, and the organic ammonium salt reacts with the inorganic salt to form a perovskite light-absorbing layer, and the solvent comprises a first solvent and a second solvent, wherein the first solvent is an alcohol solvent, and the second solvent is a polar solvent containing lone pairs of electrons of N or O atoms, and the content of the second solvent is less than the content of the first solvent; S04 preparing a second carrier transport layer on the perovskite light absorption layer, or preparing a second intermediate layer on the perovskite light absorption layer and then preparing the second carrier transport layer; S05: preparing a transparent electrode on the second carrier transport layer or preparing a transparent electrode after preparing a third intermediate layer on the second carrier transport layer.